Long-term speech and swallowing function after primary resection and sentinel node biopsy for early oral squamous cell carcinoma. (February 2019) - Romer, C.A.E.; Broglie Daeppen, M.A.; Mueller, M.; Huber, G.F.; Guesewell, S.; Stoeckli, S.J.
Highlights: Minimally invasive treatment is suggested for early stage OSCC. Minimally invasive treatment is transoral resection without reconstruction and SNB. This treatment results in excellent oral function and QoL. Abstract: Objectives: Analysis of long-term speech and swallowing function and subjective quality of life (QOL) after primary resection and sentinel node biopsy (SNB) in patients with early stage (cT1/T2) oral squamous cell carcinomas (OSCC). Material and Methods: Eighty-one consecutive patients treated primarily by transoral resection without flap reconstruction and SNB for a cT1/T2 OSCC were included. Completion neck dissection (CND) was indicated in case of occult disease in the sentinel nodes. Adjuvant radiation (aRT) was administered according to the ultimate lymph node status. All patients showed no evidence of disease at time of analysis. Speech and swallowing function were assessed using standardized clinical examinations (11-item, articulation test) and validated questionnaires on subjective QOL (MDADI, FIGS). Median follow-up was 60 months (range 13–159 months) after initial treatment. Results: In all assessments for speech and swallowing, the entire study cohort achieved very high scores, with mean values located in the highest 10% of the scales. Neither tumor size nor site, age, pN-category, CND, and aRT had significant impact on functional outcomes and subjective QOL with the exception of lower scores in the global and physical scores of MDADI after CND or aRT, and articulation in the population over 60 years of age. Conclusion: Transoral resection without reconstruction and SNB for early OSCC achieves excellent outcome with regard to speech, swallowing and subjective QOL.